Factors associated to suicide risk in stricto sensu postgraduate students: a cross-sectional study - Evelyn Kelly das Neves Abreu; Samira Reschetti Marcon; Mariano Martínez Espinosa; Moisés Kogien; Marília Duarte Valim; Frantielen Castor dos Santos Nascimento
Objective: to analyze factors associated to suicide risk in postgraduate students. Method: a cross-sectional analytical study, developed with 565 stricto sensu postgraduate students from August to September 2019. Data collection took place using a validated instrument containing demographic, socioeconomic, health and academic variables; as well as variables of Module C of the Mini International Neuropsychiatric Interview (MINI), version 5.0; of the CAGE (Cut down, Annoyed by criticism, Guilty and Eye-opener) questionnaire; and the Depression, Anxiety and Stress Scale (DASS-21). Descriptive and multiple statistical analysis was performed using the Poisson regression model, with a significance level of 5%. Results: 40.8% prevalence of current suicide risk. The following variables were associated to current suicide risk: age > 30 years old (p=0.029), absence of faith (p=0.015), depression (p<0.001) and anxiety (p=0.018) symptoms, use of psychotropic drugs during the course (p<0.001), not having a meaningful and inspiring academic work (p=0.013), not having a good relationship with colleagues from the postgraduate school (p=0.033), having family relationship impaired by the demands of the postgraduate school (p=0.036) and concern about the financial situation (p=0.048). Conclusion: a high prevalence of current suicide risk was identified among postgraduate students, as well as a significant association of this risk with demographic, socioeconomic, academic and health variables.